MODERN MARKERS OF INFLAMMATION AND THEIR DIAGNOSTIC SIGNIFICANCE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Inflammation is a complex local vascular-mesenchymal response to tissue damage caused by various agents. Particularly extensive inflammatory processes develop after extensive thermal burns.